Corporate Governance And Firm Performance: The Moderating Role Of Chief Executive Officer Power In Jordan - Aldegis, Ahmad Mohammad Hasan (2024)
Corporate governance has increasingly become a key factor in firms' performance in the last few decades. In the jordanian context, the amman stock exchange (ase) has made several regulatory changes, issuing corporate governance mechanisms in 2017. However, due to the poor performance in the industrial and service sectors, jordan has faced business and social challenges since the arab uprising, which required identifying key factors influencing firm performance. Therefore, it is necessary to find mechanisms to control the efficiency of firm performance. This thesis focused on three major elements: corporate governance mechanisms, firm performance, and ceo power. The current study examines the effect of corporate governance mechanisms (board of directors’ characteristics, audit committee characteristics, risk management committee characteristics, family ownership, and arab foreign ownership) on firm performance based on the agency and resource dependence theories. Moreover, the study also identifies the influence of ceo power as a moderating variable in the relationship between the board of directors’ characteristics, audit committee characteristics, risk management committee characteristics, and firm performance. Based on agency and resource dependence theories, a conceptual model is developed and tested using the mono-method data from the 67 companies.